I think this is an easy question, but I'm obviously forgetting something.
There are two points in the first quadrant. The question is in the form of a picture (no numbers), but the points look something like A=(2,4); B=(5,1). Then it asks where point C would be if C=A-B.
I thought the answer would be C = (XsubA-XsubB , YsubA - YsubB) = (2-5 , 4-1) = (-3,3), which would place it in the second quadrant. But the answer key has it in the fourth quadrant. What am I doing wrong?
Thanks for the reply!
So does that mean that in general, C=A-B would be calculated by
C = (XsubB-XsubA, YsubB - YsubA)
C = (XsubA-XsubB , YsubA-YsubB)
It's hard for me to understand why it would work that way. Or was there just a typo in the question (or answer key) that I was given?